THE ROLE OF PHARMACY, HOSPITAL MANAGEMENT AND HEALTH INFORMATICS IN ADHERENCE TO MEDICAL TREATMENT AMONG DIABETIC PATIENTS - Saeed mohammed Abdullah Alzahrani; Hashim Hamed Abdullah Alshamrani; Thaar murdhi al Qahtani; Anas Ali Mansi Alzahrani; Abdullah Ahmed Salem alqarni; Saleh abdullah al-awadh; Ahmed Mohammed Alamri; Mohammed Hamdan Shaddad Alshamrani; Badr Ali Alharthi; Walid Awadallah Saad Al Harithi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Adherence to medical treatment is crucial for managing type 2 diabetes effectively and improving health outcomes. Nonadherence can lead to complications, increased healthcare costs, and decreased quality of life for patients. Understanding the factors influencing adherence and the roles of various healthcare professionals is essential for developing effective interventions. Objectives: This research article aims to assess the level of adherence to medical treatment among type 2 diabetes patients, identify factors influencing adherence, explore the impact of adherence on health outcomes and quality of life, evaluate interventions for improving adherence, and make recommendations for healthcare providers and policymakers. Additionally, the study aims to evaluate the roles of pharmacy, health informatics, and hospital management in promoting adherence to medical treatment. Conclusion: Factors such as health literacy, patient-related issues, and environmental barriers significantly impact treatment adherence among type 2 diabetes patients. The study emphasizes the crucial roles of medical secretaries, pharmacy technicians, pharmacists, health informatics, and hospital management in supporting patients and improving adherence. Addressing these factors and roles can enhance adherence to medical treatment, leading to better health outcomes and quality of life for type 2 diabetes patients. By implementing targeted interventions and promoting collaboration among healthcare providers, policymakers can work towards improving adherence and ultimately enhancing the overall well-being of individuals with type 2 diabetes.